1980
DOI: 10.1002/pssb.2221000219
|View full text |Cite
|
Sign up to set email alerts
|

Semi‐Empirical Calculations of the Configuration and Electronic Structure of Lithium‐Related Defects in Silicon

Abstract: A modified extended Huckel theory method is employed to perform calculations for the lithium defect in silicon model crystals with and without vacancies. The energetically stable positions for the lithium atom appear to be the tetrahedral interstitial in models without vacancies; in the case of vacancies the substitutional position is preferred. The migration energy is found to be in the same range as experimental predictions. In models with no vacancy defects the electronic defect level is established to be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1982
1982
2010
2010

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…DeLeo et al compared the hydrogen-vacancy and alkali-metal-vacancy complexes in bulk Si using a selfconsistent-field scattered-wave Xα cluster method and found that Li atoms did not passivate intrinsic vacancy defects but instead provided an electron to negatively charge the vacancy [22]. Finally, Singh calculated the Li-related defects in crystalline Si using the extended Hückel theory method with and without the vacancy, but this semi-empirical method cannot relax the structure fully so the conclusion is not credible [23].…”
Section: Introductionmentioning
confidence: 99%
“…DeLeo et al compared the hydrogen-vacancy and alkali-metal-vacancy complexes in bulk Si using a selfconsistent-field scattered-wave Xα cluster method and found that Li atoms did not passivate intrinsic vacancy defects but instead provided an electron to negatively charge the vacancy [22]. Finally, Singh calculated the Li-related defects in crystalline Si using the extended Hückel theory method with and without the vacancy, but this semi-empirical method cannot relax the structure fully so the conclusion is not credible [23].…”
Section: Introductionmentioning
confidence: 99%